Aksesibilitas Pelayanan Publik bagi Penyandang Disabilitas pada Pemerintah Daerah Kabupaten Tangerang - Ahmad Kolyubi; Suwaib Amiruddin; Riswanda Riswanda (Asosiasi Ilmuwan Administrasi Negara (ASIAN), 2024)
In this study, there is an identification of a gap between what is expected and the actual reality in the efforts of the Tangerang district government in fulfilling the rights of persons with disabilities. This gap, which is called das sein and das sollen, encouraged researchers to make a thesis on the issue. The purpose of this study is to provide a detailed description of the level of accessibility of public services available to individuals with disabilities within the Tangerang Regency local government. Zeithaml, Parasuraman, and Berry (as cited in Hardiansyah, 2018: 63) propose that to assess the quality of service actually perceived by consumers, there are specific indicators of service quality that can be categorised into five categories of service quality, namely tangible, reliability, responsiveness, assurance, and empathy. The results of this study have several points 1) Incomplete regulations or technical implementation standards for public services for persons with disabilities in the form of Tangerang Regent regulations as guidelines for the implementation of Tangerang Regency PERDA No. 11/2018 concerning the protection and fulfilment of the rights of persons with disabilities; 2) The attitude of government officials towards persons with disabilities The government is one of the important actors in the successful implementation of public service accessibility for persons with disabilities. 3) Attitudes of non-disabled people towards people with disabilities and people with disabilities towards non-disabled people In addition to the government as an important actor in the successful implementation of accessibility of public services for persons with disabilities, non-disabled people have an important part in the successful implementation of public service accessibility for persons with disabilities. Suggestions for the Tangerang Regency Government, especially public service providers from the executive branch, to immediately make a Tangerang Regent Regulation (PERBUP) regarding the fulfilment of the rights of persons with disabilities so that it can become a guideline and technical guidance for all public service providers.